2018
DOI: 10.47203/ijch.2018.v30i01.005
|View full text |Cite
|
Sign up to set email alerts
|

A study of malnutrition and associated risk factors among children of age 06-59 months in rural area of Jabalpur district, Madhya Pradesh

Abstract: Background: “Malnutrition is a silent emergency”. Malnutrition is not only an important cause of childhood mortality and morbidity, but also leads to permanent impairment of both physical and mental growth of those who survive. Aims & Objectives: To determine the prevalence of malnutrition and association with various risk factors among children of age 06-59 months in rural area of Jabalpur district Madhya Pradesh. Material and Methods: Study was conducted among 517 children of age group 06-59 months in tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…In the current study more children were affected with undernutrition when initiated into complementary feeding after six months of age. The results were consistent with the findings reported by Shukla et al (2018) who observed the prevalence of underweight children was more 37.0% when initiated into complementary feed after six months as compared to 23.8% when done at or during six months of Age (10). The present study also reported higher prevalence of underweight children when not receiving extra diet after an episode of illness.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study more children were affected with undernutrition when initiated into complementary feeding after six months of age. The results were consistent with the findings reported by Shukla et al (2018) who observed the prevalence of underweight children was more 37.0% when initiated into complementary feed after six months as compared to 23.8% when done at or during six months of Age (10). The present study also reported higher prevalence of underweight children when not receiving extra diet after an episode of illness.…”
Section: Discussionsupporting
confidence: 93%
“…In this study it was found that undernutrition was more prevalent among children born at home and the findings were in accordance with observations made by Ambaedkar et al (2016) (8) who reported that less children were malnourished when born through institutional delivery. The current study noted that the prevalence of underweight children was more when partially immunized and; the findings were consistent to children from Jabalpur (10) district where children with incomplete / partial immunization were more affected by malnutrition as compared to those with complete immunization. The present study reported significantly higher prevalence of underweight children when not breast fed exclusively for the first six month of life.…”
Section: Discussionsupporting
confidence: 85%
“…The quality of the complementary foods given to children have an impact on their health status, the diet must be diversified within the seven recommended food items by WHO [20], also Frempong and Annim [20] reported that 25% of the children who ate at least four of recommended food items were stunted. Pratim [21] found full immunization to be protective against stunting, and Shukla, et al [22] reported that incomplete immunization was a risk factor to stunting.…”
Section: Child Caring Practicesmentioning
confidence: 99%
“…According to UNICEF-WHO-WB Joint Child Malnutrition Estimates inter-agency group, about 22.3% of all children under five years old age were stunted globally, it was estimated that 148.1 million children under five years of age were too short for their age (stunting) globally in 2020. UNICEF, WHO, World Bank global and regional child malnutrition estimates [3] reveal that we are still far from a world without malnutrition due to insufficient progress to reach the World Health Assembly targets set for 2025 and the Sustainable Development Goals set for 2030.…”
Section: Introductionmentioning
confidence: 99%
“…7 Undernutrition, including stunting, wasting, and underweight, is a kind of malnutrition described by the United Nations Children's Fund as the "silent emergency". [9][10][11] Due to barriers to obtaining a healthy, balanced diet and essential health and nutrition services, the number of malnourished children rose dramatically during this COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%